Chinese herbal injections versus intrapleural cisplatin for lung cancer patients with malignant pleural effusion: A Bayesian network meta-analysis of randomized controlled trials - Xu, Yi-Fang; Chen, Yun-Ru; Bu, Fan-Long; Huang, Yu-Bei; Sun, Yu-Xin; Li, Cheng-Yin; Sellick, Jodi; Liu, Jian-Ping; Qin, Dan-Mei; Liu, Zhao-Lan (Frontiers in Oncology, 2022)
Background: Malignant pleural effusion (MPE) is a common complication in patients with advanced lung cancer that can severely compromise the quality of life and limit life expectancy. Randomized controlled trials (RCTs) have shown that Chinese herbal injections (CHIs) may be beneficial in improving quality of life. This network meta-analysis (NMA) aims to explore several CHIs used for lung cancer patients with MPE. Methods: Seven databases were systematically searched for eligible RCTs from inception to November 2021. The primary outcome was the clinical effective rate. Secondary outcomes were the improvement rate of Karnofsky performance status (KPS) score and incidence of adverse events (AEs). The Cochrane risk of bias 2 tool was used to assess the quality of included studies. Data analysis was performed using STATA 16.0 and R software 4.1.0. Both pairwise meta-analysis and Bayesian NMA were conducted. Competing interventions were ranked using the surface under the cumulative ranking (SUCRA) probabilities. Evidence grading was evaluated using the Confidence in Network Meta-Analysis online software (https://cinema.ispm.unibe.ch/). Results: A total of 44 studies involving 2,573 patients were included. The combined Huachansu injection (HCS) with intrapleural cisplatin (cis-diamminedichloro-platinum, DDP) had the highest probability of improving the clinical effective rate (SUCRA, 84.33%). The Kangai injection (KA) combined with DDP had the most improvement rate of KPS score (SUCRA, 80.82%), whilst the Fufangkushen injection (FFKS) alone was more likely to reduce AEs including gastrointestinal reactions (SUCRA, 89.92%), leukopenia (SUCRA, 91.85%) and chest pain (SUCRA, 98.17%). FFKS combined with DDP ranked the best in reducing the incidence of fever (SUCRA, 75.45%). Conclusions: Our NMA showed that CHIs alone or combined with DDP could improve clinical effectiveness and quality of life and reduce AEs, compared to DDP alone. HSC and KA, combined with DDP, may be the most effective considering clinical effective rate and improvement of KPS score, respectively. FFKS, either used alone or in combination therapy with DDP, may be the best in reducing AEs. However, high-quality RCTs with larger sample sizes are needed to further support the evidence.